Degradation of deep ultraviolet photoresist by As‐implantation studied by Ar‐cluster beam profiling. (1st August 2012) - Conard, T.; Franquet, A.; Tsvetanova, D.; Mouhib, T.; Vandervorst, W.
<x xml:space="preserve">Abstract</x> Wet processes are gaining a renewed interest for removal of high‐dose ion‐implanted photoresist (II‐PR) in front‐end‐of‐line semiconductor manufacturing because of their excellent selectivity towards the wafer substrate and gate materials. The selection of wet chemistries is supported by an insight into the resist degradation by ion implantation. TOF‐SIMS has been applied for characterization of the chemical changes in 248 nm deep UV photoresist after arsenic implantation. The cross‐linking of the resist is dominant, especially for high doses and energies. It leads to significant depletion of hydrogen and formation of carbon macroradicals that recombine to form C‐C cross‐linked crust. A series of implanted samples were depth profiled using O2, Cs, C60 and an Ar‐cluster beam as sputter species in order to analyze the chemical modifications inside the crust layer. Whereas in the implanted region, no sputter conditions providing molecular information have yet been identified, in the non‐implanted region, many molecular ions are identified when profiling using Ar‐clusters as sputter ions. Neither O2, Cs nor C60 sputtering would lead to molecular information in this region either. In particular with Ar‐clusters, very large differences in sputter rates have also been observed between the implanted and non‐implanted region, as well as a significant matrix effect in the implanted region. These differences are linked to the level of cross‐linking present in the crust layer. Copyright © 2012 John Wiley & Sons, Ltd.